2016
DOI: 10.1002/ijfe.1545
|View full text |Cite
|
Sign up to set email alerts
|

What Does Rebalancing Really Achieve?

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Subsequent studies support these findings by concluding that rebalancing strategies enhance the Sharpe ratio of a portfolio (see, e.g., Harjoto and Jones 2006;Dichtl et al 2016). In contrast, Cuthbertson et al (2015) question the benefits of periodical rebalancing in presence of transaction costs and propose to rebalance not more than necessary to keep a portfolio's asset allocation adequately close to the target percentages over time. A detailed analysis of the role of transaction costs for rebalancing strategies is provided by Donohue and Yip (2003).…”
Section: Related Literaturementioning
confidence: 99%
“…Subsequent studies support these findings by concluding that rebalancing strategies enhance the Sharpe ratio of a portfolio (see, e.g., Harjoto and Jones 2006;Dichtl et al 2016). In contrast, Cuthbertson et al (2015) question the benefits of periodical rebalancing in presence of transaction costs and propose to rebalance not more than necessary to keep a portfolio's asset allocation adequately close to the target percentages over time. A detailed analysis of the role of transaction costs for rebalancing strategies is provided by Donohue and Yip (2003).…”
Section: Related Literaturementioning
confidence: 99%
“…In this scenario, after capital has been invested, no interim transactions take place until the account is closed, regardless of market fluctuations (Dichtl et al, 2016). This procedure is also known as the buy‐and‐hold approach (Cuthbertson et al, 2016). As a second approach, we investigate how the results change when all the robo‐managers use the most frequently observed procedure of threshold‐based rebalancing with a limit value of 10%.…”
Section: Results Of the Econometric Studymentioning
confidence: 99%
“…In general, the results indicated that while rebalancing reduces volatility and momentum effects, the buyand-hold strategy outperformed them due to the relatively higher returns offered by stocks compared to the risk-free asset. Cuthbertson et al (2016) studied the effects of portfolio rebalancing on their returns and risks. The authors aimed to identify the misleading claims associated with rebalanced strategies and demonstrated, through theoretical analysis and simulations, that the apparent advantages of rebalanced strategies over infinite time horizons do not accurately reflect their performance over finite time horizons.…”
Section: Related Workmentioning
confidence: 99%